THE ROLE OF PARENT-CHILD RELATIONSHIPS IN THE FORMATION OF PSYCHOSOMATIC DISORDERS - Светлана Альбертовна Дракина; Нина Константиновна Перевощикова; Галина Петровна Торочкина (The Publishing House Medicine and Enlightenment, 2017)
Modern family and its problems are the object of study of several Sciences: medicine, psychology, pedagogy, sociology, demography, Economics. From the nature of the parent-child relationship depends on how the game will develop the child's relationship with the world, what position in life will choose already grown kid and then an adult. Parental support is important at any age, as the deficit becomes the cause of pronounced mental and physical maturation of the child, the disintegration of affection as the most important factor of mental development, maladjustment, psychosomatic disorders. In the article the importance of child-parent relationship is demonstrated on the example of classical psychosomatic diseases - bronchial asthma. The purpose of the study - defining the role of parent-child relationships in the implementation of bronchial asthma in children. Material and methods. To identify various psychological deviations in the relationship of parents to children and causes of these violations were used in the questionnaire «Analysis of family relations» as E.G. Eidemiller, W. Justices. In assessing psychological status were studied personality traits of adolescents using a multi-factor questionnaire by R.B. Kettell. Local alarms - school, interpersonal, self-assessment, the magic were determined using questionnaire A.M. Prichoschan. Conclusion. Pathogenic in most cases, the parent-child relationship is highly correlated with personal traits of adolescents that stresses the leading role of the family in shaping the character of a teenager, his relationship to the disease, the level of trust in adults. An integrated approach to the rehabilitation of adolescent patients with asthma using interagency collaboration has allowed to improve the quality of their training in the «Asthma-school». Conducting corrective treatment contributed to the improvement of psycho-emotional status of adolescents, the normalization they have a trusting relationship with parents and the doctor, which further allowed us to regain control over the course of the disease.